2016
DOI: 10.1136/bjophthalmol-2015-307989
|View full text |Cite
|
Sign up to set email alerts
|

Functional–morphological parameters, aqueous flare and cytokines in macular oedema with branch retinal vein occlusion after ranibizumab

Abstract: These findings suggest that the aqueous flare is associated with inflammatory factors/cytokines, and that the change of the aqueous flare value may influence the long-term prognosis in patients with BRVO receiving IRI therapy for macular oedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
(16 reference statements)
1
17
0
Order By: Relevance
“…Miyake et al [25] showed that both aqueous flare intensity and inflammatory cytokines were higher in eyes with macular edema due to retinal vein occlusion than in controls. In keeping with these findings, other studies have demonstrated significant correlations between a change in flare intensity and improvement of central macular thickness in eyes with retinal vein occlusion [26-28].…”
Section: Discussionsupporting
confidence: 75%
“…Miyake et al [25] showed that both aqueous flare intensity and inflammatory cytokines were higher in eyes with macular edema due to retinal vein occlusion than in controls. In keeping with these findings, other studies have demonstrated significant correlations between a change in flare intensity and improvement of central macular thickness in eyes with retinal vein occlusion [26-28].…”
Section: Discussionsupporting
confidence: 75%
“…; Noma et al. ). Aqueous flare remained slightly elevated in the postoperative only treatment group at 3 months and it may be important for clinical practice regarding late occurrence of macular oedema.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, aggressive VEGF blockade prevents the progression of RNP and promotes reperfusion by controlling the positive feedback loop [71]. In addition, the aqueous flare value showed a significant decrease at both 1 and 6 months after anti-VEGF therapy [77], suggesting that this therapy inhibited inflammation. Accordingly, anti-VEGF therapy seems to improve retinal hypoxia and inflammation in BRVO patients by inhibiting both VEGF and inflammatory cytokines to suppress leukocyte chemotaxis and adhesion in the retinal vessels.…”
Section: Possible Mechanism Of Macular Edema In Brvomentioning
confidence: 99%